Implementation of Culamega Health Center Head Regulation No: KP.11/KEP.097/PKM.CLMG/I/2023 on No-Smoking Areas (KTR) - Buhori, Raja Muhammad Rafian (BKM Public Health and Community Medicine, 2024)
Purpose: To protect employees and visitors from the hazards of cigarette smoke in the Culamega Health Center environment. Methods: The No-Smoking Area (KTR) is a designated area where smoking or tobacco-related activities are prohibited. The establishment of KTR aims to uphold the right to public health and provide a clean environment and healthy air, thereby ensuring that employees and visitors feel protected by this regulation. The Culamega Health Center has enacted Regulation No: KP.11/KEP.097/PKM.CLMG/I/2023 concerning KTR. This policy aims to protect employees and visitors from the harmful effects of smoking and to ensure clean air rights for them. However, the implementation of the KTR policy at the Culamega Health Center has not been fully effective. This is evidenced by the continued smoking by some employees and visitors within the health center premises, despite existing no-smoking signs and media. The low compliance with this regulation may be due to inadequate socialization and enforcement of the rules. Results: To optimize the implementation of the KTR policy at the Culamega Health Center, efforts such as education on the dangers of smoking and the benefits of not smoking, the formation of monitoring teams to oversee violations, and the imposition of sanctions according to the regulations are necessary. Consistent and strict rule enforcement is expected to create a deterrent effect for violators and encourage compliance among all health center employees and visitors. Additionally, budget support for health promotion activities will play a significant role in the successful implementation of KTR at the Culamega Health Center. Conclusion: With consistent and stringent enforcement, it is hoped that compliance with the KTR policy will improve, thereby ensuring a healthier environment for all employees and visitors at the Culamega Health Center.